2012
DOI: 10.3111/13696998.2012.698671
|View full text |Cite
|
Sign up to set email alerts
|

Direct medical costs associated with atopic diseases among young children in Thailand

Abstract: Atopic diseases in young children are associated with substantial burden in direct medical costs to Thailand. These costs can be diminished through nutritional intervention recognized to effectively decrease the incidence of atopic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…86 Monitoring and laboratory tests were associated with a cost of ฿962; inpatient care had a cost of ฿564. 86 These relatively small costs compared with the cost in some other countries may in part be a result of climate differences: Thailand weather is generally warm with a high degree of humidity, possibly aiding in keeping the skin hydrated. 86 Last, in the first study of its kind conducted in India, the costs associated with AD in an outpatient setting showed that mean total cost over a 6-month period (calculated as the sum of the mean caregiver cost, provider cost and indirect costs) was found to be`6235.…”
Section: Economic Burdenmentioning
confidence: 99%
“…86 Monitoring and laboratory tests were associated with a cost of ฿962; inpatient care had a cost of ฿564. 86 These relatively small costs compared with the cost in some other countries may in part be a result of climate differences: Thailand weather is generally warm with a high degree of humidity, possibly aiding in keeping the skin hydrated. 86 Last, in the first study of its kind conducted in India, the costs associated with AD in an outpatient setting showed that mean total cost over a 6-month period (calculated as the sum of the mean caregiver cost, provider cost and indirect costs) was found to be`6235.…”
Section: Economic Burdenmentioning
confidence: 99%
“…A total of 26 studies (33%) were considered to have conducted a form of cost‐of‐illness study, one of which used a model developed in Excel (Microsoft, Redmond, WA, U.S.A.) . Most of these studies evaluated the cost of eczema within children, with only two papers stating explicitly that they were evaluating adults with eczema . Other papers did not specify the population age, with 11 stating a population of patients with eczema .…”
Section: Resultsmentioning
confidence: 99%
“…The lowest costs were observed in Thailand [35] (USD 199 across all severities, ranging from USD 124 among mild cases to USD 968 among severe cases), in part because only direct costs were reported.…”
Section: Economic Burden Of Pediatric Ad In the Asia Pacific Regionmentioning
confidence: 99%
“…A total of 5 published studies were identified (table 1): 2 for Australia [32,33], 1 for South Korea [34], 1 for Thailand [35] and 1 for the Philippines [36], which required reanalyses to generate some of the outcomes presented herein. These studies were further complemented with unpublished analyses conducted by some of the coauthors in Indonesia, Malaysia and Singapore [37].…”
Section: Economic Burden Of Pediatric Ad In the Asia Pacific Regionmentioning
confidence: 99%